CONTRIBUTION OF REGIONAL TAXES AND REGIONAL LEVIES TO REGIONAL ORIGINAL INCOME IN BUOL DISTRICT: KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH DI DISTRIK BUOL - Syafrudin, Febriani; Naharudin, Andi; Fathur, Alfansyah; Yanto, Edi (STIE MUJAHIDIN TOLITOLI, 2024)
This research aims to determine the contribution of regional taxes and regional levies to original regional income in Buol Regency. This research uses quantitative research. The data source is secondary data, namely data obtained through observation, interviews and documentation related to this research. The data analysis method used is Growth Rate Analysis. Based on the research results, it was concluded that according to the data obtained, the contribution of regional tax revenues increased in 2019 and 2021, while in 2018, 2020 and 2022 there were symptoms of fluctuation in each type of tax. Then the contribution of Regional Levies experiences fluctuating changes every year. Therefore, regional tax revenues contribute to original regional income, while regional levies contribute less to original regional income.